FRI0218 Safety of Non Anti-TNF Biologic Agents in Rheumatic Patients with Past Hepatitis B Virus Infection. A Single-Center Real-Life Study. (15th July 2016) - Papalopoulos, I.; Kougkas, N.; Avgoustidis, N.; Repa, A.; Fanouriakis, A.; Sidiropoulos, P.
Abstract : Background: The safety of newer non anti-TNF biologic agents [abatacept (ABA), tocilizumab (TCZ) and rituximab (RTX)] in patients with autoimmune rheumatic diseases and past HBV infection [defined as HBsAg(−), anti-HBc(+), anti-HBs(±)] has not been firmly established. Objectives: To assess the safety [reactivation of hepatitis B virus (HBV)] of non anti-TNF biologic agents in patients with serologic evidence of past HBV infection in real-life clinical settings. Methods: Retrospective chart review of patients followed in the Department of Rheumatology of the University Hospital of Crete. Patients who received ABA, TCZ or RTX during the period 2005–2015 and were HBsAg(−), anti-HBc(+), anti-HBs(±) at baseline were identified and reviewed for cases of HBV reactivation (defined as increased ALT accompanied by an increase of serum HBV DNA levels by >1 log10 compared with baseline or a switch in HBV DNA detection from negative to positive). Changes in anti-HBs titers during biologic therapy in patients who were anti-HBs(+) at baseline were also documented. Results: 83 different cases of non anti-TNF biologic therapy (34 ABA, 26 RTX and 23 TCZ) from 58 patients (56 RA - 2 ANCA-associated vasculitis) were identified. 64 cases (77.1%) were anti-HBc(+) anti-HBs(+) and 19 (22.9%) were anti-HBc(+) anti-HBs(−). Mean (SD) age at disease diagnosis and at non anti-TNF initiation was 53.6 (13.1) and 63.4 (9.2) years, respectively. All cases with RA had received prior anti-TNF agents [mean (SD) number of anti-TNF agents 1.1 (0.8)]. During treatment with non anti-TNF, concomitant synthetic disease modifying drugs or glucocorticoids were received by 91.5% and 46.3% of cases, respectively. Only 7 cases (8.4%) received antiviral prophylaxis concomitant with non anti-TNF treatment (4 with lamivudine - 3 with entecavir). After a mean (SD) of 41.9 (24.6) months of follow-up and a mean (SD) of 18.0 (15.9) therapy cycles, one anti-HBc(+) anti-HBs(−) case experienced HBV reactivation 12 months after treatment with abatacept and was treated with tenofovir with good outcome. Of anti-HBs(+) patients at baseline, titers of anti-HBs antibodies did not show statistically significant delay from baseline to most recent follow-up (456.9 mIU/ml vs. 390.7 mIU/ml, respectively, p=0.08) (Figure 1 ). Conclusions: One case of HBV reactivation underlines the need for diligent monitoring in patients with serologic evidence of past HBV infection receiving non anti-TNF biologic agents. More data are needed to determine the need for universal prophylactic antiviral therapy in this subset of patients. Disclosure of Interest: None declared